Metatranscriptomic analysis reveals two new viruses and highly expressed endogenous elements in pepper in Iraq - Shurooq Zagier; Osamah Alisawi; Wisam Aljuaifari; Fadhal Al Fadhal (Universitas Lampung, 2026)
Pepper plants exhibiting severe leaf curling and deformation in open fields in Iraq were investigated to characterize their associated virome using metatranscriptomic sequencing. High-throughput sequencing (HTS) revealed the presence of bell pepper alphaendornavirus (BPEV) and pepper cryptic virus 2 (PCV-2), together with fragmented sequences related to tobacco vein clearing virus (TVCV). A nearly complete genome of the Iraqi BPEV isolate (14,700 bp) and both genomic segments of PCV-2 (1,623 bp and 1,513 bp) were assembled and deposited in GenBank. Phylogenetic analysis showed that the BPEV isolate clustered closely with isolates from South Korea, Jamaica, and the Dominican Republic, whereas both PCV-2 genomic segments were most closely related to Turkish isolates, indicating high genetic conservation among geographically distant populations. In addition, transcriptome mapping revealed abundant expression of ten endogenous pararetroviral elements integrated within the pepper genome, with most transcripts corresponding to reverse transcriptase (RT-LTR) and RNase H domains. This study represents the first comprehensive metatranscriptomic characterization of the pepper virome in Iraq, documenting the first detection of BPEV and PCV-2 in the country while revealing extensive expression of endogenous viral elements. These findings expand current knowledge of pepper-associated viruses in the Middle East and demonstrate the value of metatranscriptomic sequencing for detecting both exogenous viruses and endogenous viral components.